Water quality evaluation using physicochemical and biological indices to characterize the integrity of the Orogodo River in sub-Saharan Africa - Olomukoro, John Ovie; Obi-Obueze, Nwamaka Ogochukwu; Eko-Imirianye, Rukeme; Anani, Osikemekha Anthony; Obot, Victoria (Frontiers in Environmental Chemistry, 2022)
The preliminary consequence of pollutants in water is to reduce the quality of chemicals in the water although this may not be immediately noticeable because of the self-purifying ability of some water bodies. The study of the physicochemical characteristics, bacteriological and macrobenthic invertebrates was carried out in the Orogodo River. All the examined physicochemical characteristics of the water showed no significant difference (p>0.05) across the stations. For the heavy metals, it was in this decreasing order; station 2> station 3> station 1. All the heavy metals except Nickel had high values in upstream (station 1). Bacteriological examination of the water revealed mesophilic bacteria across the stations at p<0.01 (a highly significant difference). E. coli varied significantly (p<0.01) across the stations. However, a further evaluation using the DMR test reveals that the population recorded at station 3 was significantly higher than those at stations 1 and 2. A total of 787 macrobenthic invertebrates comprising 44 macro invertebrates’ taxa were recorded. Most of the macrobenthic fauna observed were distributed across the three stations except the chironomids, the rat-tailed maggot (Eristalis tenax), and the family Hirudinea whose occurrence was almost restricted to station 2. This revealed ecological impact because this species is a basic indicator of an ecosystem sentinel. Sorenson's quotient of faunal similarity showed that macrobenthic fauna at the three stations was similar. The similarity was highest between stations 1 and 3 (75.0%) and lowest between stations 1 and 2 (50.0%). The Biological Monitoring Working Party (BMWP) score system showed that station 2 was moderately polluted while stations 1 and 3 were only slightly impacted. At stations 1, 2, and 3, the arithmetic WQI (water quality) values were 900.99, 1010.10, and 951.20 respectively. The high values of WQI obtained across the stations were attributable to the concentrations of Fe, Cu, Cr, Cd, Ni, Pb, V, and THC. Thus, reiterating the conclusion drawn from the physicochemical parameter analysis. Boiling of the water before consumption is highly recommended to avoid possible human health problems.